An integrated software-hardware exercise encouraging system / Kong Sibo - Kong , Sibo (2022)
With the rapid development of technology, transportation, and urbanization, people’s physical requirement is greatly reduced, and the mental load of many jobs is increased at the same time. Young people are now more likely to sit in front of a screen than go out for exercise. Lack of physical activity leads to an increased risk of a variety of chronic diseases, such as obesity, diabetes, and cardiovascular disease. This study proposed an integrated system for physical exercise, comprising an exercise monitoring wearable device and an exercise encouraging mobile application. The developed system captures the users’ heart rate, blood oxygen and body temperature in real-time while the users are exercising. The STM32F103 board was used as the main control chip, the MAX30102 sensor for collecting users’ heart rate and blood oxygen, whereas the MAX30205 sensor for collecting users’ body temperature. Bluetooth low power module was chosen for communication with Android. Android Studio was used as the software development tool for the mobile application that receives sensor signals and records the signals as data. Analysis and visualization of data, as well as risk alerting, are among the functions of the mobile application. The application encourages exercise through exercise reminder, exercise goal setting, sign in, and other features. After implementing the system, 10 participants aged 18-30 years old were recruited for a six-week experiment using qualitative and quantitative methods. The study first assessed the effectiveness of the developed integrated system in encouraging exercise among the participants. Next, the importance of the exercise monitoring wearable device in encouraging exercise was studied. Finally, the effectiveness of the system in maintaining the participants’ active lifestyle was studied. The results show that the system was effective in improving and maintaining participants’ physical activity and the wearable device played a role in encouraging physical activity. The participants also reported little to no discomfort when using the system.